Impact of saline loading at cardiac catheterization on the classification and management of patients evaluated for pulmonary hypertension. (1st May 2020) - Moghaddam, Nima; Swiston, John R.; Weatherald, Jason; Mielniczuk, Lisa; Kapasi, Ali; Hambly, Nathan; Langleben, David; Brunner, Nathan W.
Abstract: Background: The extent to which saline loading (SL) during cardiac catheterization influences clinical practice in pulmonary hypertension (PH) is unknown. We surveyed a national cohort of PH specialists to determine how SL affected diagnosis and management. Methods: Relevant clinical and hemodynamic data pre-SL for patients with a baseline pulmonary arterial wedge pressure (PAWP) ≤15 mm Hg were presented as surveys to 7 PH specialists. The specialists were asked to classify patients according to the WHO classification scheme, rate their confidence, and state their treatment plans. Hemodynamic data following 500 mL of SL was then presented, and specialists answered the same questions. A positive fluid challenge (PFC) was defined as PAWP >18 mm Hg after SL. Results: Seven specialists evaluated 48 cases, for a total of 336 surveys. SL influenced PH classification with 19.6% of cases reclassified as having a component of Group 2 PH. SL increased confidence in PH classification (mean difference 0.25; 95% CI 0.15–0.35). With a PFC, physicians were more likely to classify patients as PH due to left heart disease (OR 6.1; 95% CI 2.8–13.1), extend time to follow-up (OR 3.2; 95% CI 1.6–6.7), and discharge patients from PH clinic (OR 5.0; 95% CI 1.9–13.1). SL changed the treatment plan in 6.5% of cases, mostly with a PFC causing reconsideration in treatment initiation. Conclusion: The addition of SL to hemodynamic assessment of PH can impact physicians' classification and management decisions. However, decisions are not solely based on the SL results, but rather the entirety of the clinical data available. Highlights: Saline loading can be of clinical value in the real-world care of patients with PH. Saline loading affects physicians' PH classification, decisions for treatment, and follow-up. Saline loading results do not overrule the remainder of the PH workup.